A aprendizagem empreendedora pela opinião de colaboradores de instituições financeiras - Santos, Flávia Fernandes dos (2024)
Entrepreneurial learning is a dynamic process that involves both the development of competencies and the ability to adapt and innovate through practical experience and reflection on challenges faced. This study aims to understand how entrepreneurial learning takes shape in financial institutions. To achieve this objective, a qualitative approach was used, based on eight interviews with employees from different financial institutions in the eastern and western regions of Paraná. Data analysis provided an in-depth view of employees' practices and perceptions regarding learning in the organizational context, considering the challenges and opportunities generated by the regulated environment in which these institutions operate. The results show that although the regulatory environment and standardized processes limit the possibility of improvements, the encouragement of continuous training and technical qualification provides a solid foundation for developing essential skills such as financial management, negotiation, and customer service. Additionally, a culture of collaborative learning and the practice of imitating external methodologies, adapted to the context of financial institutions, help enhance operational efficiency and customer service, strengthening this sector's competitiveness in the market. The interviewees highlighted the importance of continuous and up-to-date training that not only addresses the sector's needs but also equips employees to adapt to market changes and effectively meet customer demands. Despite advancements, challenges such as resistance to change and difficulties in clearly defining entrepreneurial learning affect the consistent application of improvement practices and the creation of a more open organizational culture that fosters institutional development.